ANALYSIS OF DISTURBANCES IN LOGISTIC FLOWS IN MINING MACHINERY COMPANY - Karolina PROBIERZ (Scientific Journal of Silesian University of Technology. Series Transport)
Disturbances that occur in the course of transportation and storage tasks has been identified and analyzed. Disturbances occurring the most frequently in the ongoing processes of transport and storage have been selected. The article also shows possible ways of improvements of occurring disturbances. The article is of a practical nature.